Multivariate Analysis of Factors Related to Emotional Regulation and Executive Functions in Adolescents Post Covid-19 - Adriana Sánchez-Caicedo; Erika Ruperti-Lucero; Juan Diego Valenzuela-Cobos; Fabricio Guevara-Viejó (Migration Letters, 2023)
The confinement by Covid 19 affected several aspects of the lives of human beings. In addition to the health affectation, there was evidence of havoc in the emotional life of the people, in this case the analysis is focused on the emotional regulation strategies that the adolescents were able to develop and how they were dynamized with some indicators of executive functions. By means of a multivariate analysis, the strategies of emotional regulation and the relationship with the development of ex-ecutive functions in Ecuadorian adolescents were analyzed. The instru-ments used were: Emotional Regulation Questionnaire and EFECO Scale for Executive Functions in self-report format. The results show that most adolescents use emotional regulation strategies such as cognitive reap-praisal and emotional suppression; the components of inhibition, cogni-tive flexibility, initiative, planning, working memory, monitoring, emotional control and organization of materials present high average levels, reaching an optimal development in adolescence; the emotional regulation strategies and the components of the executive functions present a positive correlation. According to the multivariate analysis, the development of executive functions is dependent on emotional regulation strategies. Cognitive reappraisal as an emotional regulation strategy is significantly related to emotional control in the study sample.